The mechanism of Girdin in degenerative brain disease caused by high glucose stimulation - Liu, Longteng; Zhang, Jinsong; Han, Yanxi; Liu, Dongge (Frontiers in Endocrinology, 2022)
Girdin, as an actin-binding protein, plays a major role in maintaining the stability of the actin skeleton structure and affects the growth, development, and migration of neurons. This study discusses the mechanism of Girdin in brain degeneration caused by high glucose stimulation. We examined the expression of Girdin in diabetic patients. The positive expression rate of Girdin in the diabetic group was 17.2% (5/29), which was obviously lower than the positive expression rate of 83.3% (20/24) in the non-diabetic group. We examined the expression of Girdin and its signaling pathway-related proteins Akt and STAT3 in hippocampal neurons induced by high glucose. The results showed that, in contrast to the control group (glucose concentration = 25 mmol/L), the expression of Girdin in the high-glucose group (glucose concentration = 225 mmol/L) was reduced (P < 0.05); the phosphorylation levels of Akt and STAT3 related to Girdin signaling pathway were also reduced (P < 0.05). Under high-glucose stimulation, the structure of neurons is abnormal, such as the reduction or disappearance of dendritic spines, and the number of neurons is reduced. In addition, Girdin and Akt were less expressed in neurons and synapses, especially the most obvious reduction in synaptic terminals. The activity of Girdin and its signaling pathway-related proteins Akt and STAT3 decreased in neurons under high glucose stimulation, indicating that the mechanism of Girdin in brain degeneration caused by high glucose stimulation was closely related to the Akt and STAT3 pathways. Graphic Abstract The mechanism of Girdin in degenerative brain disease caused by high glucose stimulation. This article discusses the mechanism of Girdin in brain degeneration induced by high glucose stimulation. The expression of Girdin in the diabetic group was significantly lower than that in the non-diabetic group. The expression of Girdin and its signaling pathway-related proteins Akt and STAT3 in hippocampal neurons was significantly reduced under high glucose stimulation. Under high glucose stimulation, the structure of neurons is abnormal and the number decreases; synapses become shorter. It indicates that the mechanism of brain degeneration caused by high glucose stimulation by Girdin is closely related to the Akt and STAT3 pathways.